(untitled) (Journal of Finance, Business and Management Studies, 2024)
These research was carried out to examine the determinants of the financial system development in Nigeria using data from 2017 to 2022,generally,the financial system encompasses all financial intermediaries that operate in the financial sector of the economy categorized into the surplus and deficit spending units in which it is as well been looked into in these research study. A more regulated and better working financial sector contributes toward achieving monetary growth based on proficient resource allocation and reducing information asymmetries. The study uses annual data of Nigeria from 2017 to 2022 to examine the determinants of financial sector development in Nigeria. This period is considered long enough to shed light on the definite relationships that exist between policies of financial reform, output growth, natural resource and financial sector development. One key limitation of this study is the nature of data that would be employed for empirical analysis. The data are essentially obtained from secondary sources, and as such, results to be obtained would depend on the quality of the data. Following the introduction, section two dwells on the review of literature, while section three provides an exposition on the theoretical framework and model specification. Section four relates to empirical analysis and discussion of findings. Finally, section five recommends and concludes the paper.